The Effect of Solar Panels and Vegetation Strategy on the Sustainability of Open Spaces - Kareem Hajer Kamel; Mohammed Younis Mahmoud (Civil and Environmental Engineering)
Cities need to take serious steps to improve the living conditions of their citizens and their surrounding environment as the population of urban centers grows. Parking spaces have a clear potential to contribute to city sustainability. The research problem is that there is high energy consumption by residential buildings for multiple purposes and a significant increase in outdoor temperatures. Photovoltaic panels are a popular classification of sustainable rooftops adopted by cities around the world. This study aims to evaluate the impact of photovoltaic panels and trees in achieving sustainable development goals and combating climate change. In order to mitigate energy consumption and environmental issues related to fossil fuels and provide thermal comfort. The hypothesis of the research is that the use of renewable energy sources such as solar panels, in addition to vegetation can provide thermal comfort in addition to energy savings. The pilot study was conducted in residential complex in Iraq, Baghdad. Two different strategies and four separate scenarios were created using vegetation and photovoltaic panels. Envi-met 5.5.0 software was used to analyse and evaluate thermal comfort factors (PET, SVF) and simulated using ENVI-MET software on a summer day in July 2023. The results of the scenarios were then compared in terms of their impact on human thermal comfort. The results revealed a decrease in (PET) by (8.32) degrees Celsius, which achieved international standards for outdoor pedestrian comfort. As well as shading areas less exposed to sunlight with trees, in addition to providing shade to protect cars from weather factors, and finally providing electricity to homes.